Cascade pulse-tube cryocooler using a displacer for efficient work recovery. (September 2017) - Xu, Jingyuan; Hu, Jianying; Hu, Jiangfeng; Luo, Ercang; Zhang, Limin; Gao, Bo
Highlights: A two—stage pulse tube cryocooler using displacer as phase shifter is proposed. Cooling power is improved by 32% than sing—stage cryocooler. Exergy efficiency of 37.2% and cooling power of 371 W are achieved at 130 K. Abstract: Expansion work is generally wasted as heat in a pulse-tube cryocooler and thus represents an obstacle to obtaining higher Carnot efficiency. Recovery of this dissipated power is crucial to improvement of these cooling systems, particularly when the cooling temperature is not very low. In this paper, an efficient cascade cryocooler that is capable of recovering acoustic power is introduced. The cryocooler is composed of two coolers and a displacer unit. The displacer, which fulfills both phase modulation and power transmission roles, is sandwiched in the structure by the two coolers. This means that the expansion work from the first stage cooler can then be used by the second stage cooler. The expansion work of the second stage cooler is much lower than the total input work and it is thus not necessary to recover it. Analyses and experiments were conducted to verify the proposed configuration. At an input power of 1249 W, the cascade cryocooler achieved its highest overall relative Carnot efficiency of 37.2% and a cooling power of 371 W at 130 K. When compared with the performance of a traditional pulse-tube cryocooler, the cooling efficiency was improved by 32%.